Efek Musik Suara Alam (Nature Sounds Music) terhadap Penurunan Kecemasan pada Pasien Pasca Stroke - wulandari, Tri suraning; Kurniawati, Ratna; Azizatul Ilmiyah, Vina (STIKES Ngesti Waluyo, 2023)
Stroke refers to a disorder caused by cerebral blood flow interruption that results in neurological impairment. Brain deterioration causes anxiety and eventually results in mortality. The prevalence of anxiety in stroke (Post-Stroke Anxiety, or PSA) is 10.9%, with most of the cases occured in males and ranged from mild to moderate levels. The anxiety usually appear when daily activities cannot be done. The long-term impacts of post-stroke anxiety influence one's quality of life. Providing natural sounds music, such as music from piano, bird noises, and water bubbling sounds, is an alternative to alleviate the post-stroke anxiety. This study aims at identifying whether nature sounds music might help to reduce anxiety in post-stroke patients. Quasi-experimental design was carried out by implementing a one-group pretest-and post-test design. Post-stroke patients who had been unable to carry out everyday tasks for more than 6 months were purposively selected as research samples. Data were obtained through interviews and observations, as well as using questionnaire (The Hamilton Rating Scale for Anxiety or HRS-A). Paired T-Test was used in analyze the data. The findings showed that from 17 respondents, 11 of them (64.7%) had moderate anxiety, while the others (35.3%) had severe anxiety. The tests on varied degrees of anxiety showed the p-value of 0.000, indicating that there was difference in anxiety prior and after being given nature sounds music. The post-test mean value (18.53) was lower than that on the pre-test (21.53). To summarize, nature sounds music is good for lowering anxiety in post-stroke patients.